Ex situ conservation and cryopreservation of orchid germplasm - Merritt, D.; Hay, F.; Swarts, N.; Sommerville, K.; Dixon, Kingsley (University of Chicago Press, 2014)
Premise of research. Orchids are among the most enigmatic of plant species. Yet the Orchidaceae comprises more species at risk of extinction than any other plant family. The collection and storage of orchid germplasm-principally seeds and associated mycorrhizal fungi but also protocorm-like bodies using encapsulation and vitrification techniques-allows for secure ex situ conservation. This article reviews the approaches and techniques used for the ex situ conservation of orchid germplasm, with a focus on seed banking and the use of cryopreservation techniques to improve the longevity of germplasm. Pivotal results. It is increasingly apparent that cryopreservation-the storage of germplasm at ultra-low temperatures (e.g., in liquid nitrogen)-is required for the long-term and low-maintenance conservation of all types of orchid germplasm. For orchid seeds, desiccation tolerance is common, but longevity in storage is poor. Cryopreservation of orchid seeds shows promise, but some complexities in low-temperature storage behavior still require explanation and resolution.The application of more advanced cryopreservation techniques, including encapsulation-dehydration and vitrification, is becoming increasingly common. These techniques provide for the simultaneous storage of orchid propagules with their compatible fungus, while for seeds, vitrification techniques show potential for improving tolerance to the stresses of cryopreservation. Conclusions. A renewed focus on describing the low-temperature storage physiology of orchid seeds to more precisely define the relationship between seed water content, storage temperature, and seed survival is required, as is perhaps the wider adoption of the use of cryoprotectants for seeds. This research, coupled with the development of improved methods of seed viability testing, will support the growing work of germplasm banks to protect orchid biodiversity in the face of habitat loss and potential species extinction